EFFECTIVENESS OF THE USE OF INNOVATIVE TECHNOLOGIES IN TEACHING GERMAN - Begasheva Sharofat Nematullayevna (Galaxy International Interdisciplinary Research Journal, 2021)
This article provides a scientific overview of the teaching of German language based on innovative technologies and provides scientific information. In the course, the effectiveness of innovative technologies and their effectiveness will be further demonstrated through a number of examples.